Finite element analysis of seepage flow under a sheet pile - Loh, Ling Ping (Universiti Malaysia Sarawak, UNIMAS, 2006)
A stud y on the phenomenon of seepage flow under a sheet pile using the finite element method is pr esented . It has been hypothesized that, the usage of sheet pile is an effective way of seepage controlling measure by which it will significantly reduce the rate of seepage flow . A finite element model has been developed to analyze the seepage flow under a sheet pile. The element used was a four - node quadrilateral element. The flow domain was descretised into suitable elements and the flow potential head at each node and velocity components at each element were obtained. The total discharges of seepage flow under a sheet pile were found. The present study tends to analyze the variation of results of seepage flow under a sheet pile for three different length sheet piles with two different cases of soil conditions. A FORTRAN program was developed to analyze th e problem.